Empowering the Tayyib Principle in Halal Health Products: a Holistic Approach to Sustainable Development Goals - Nadhirah Nordin; Aam Slamet; Azie Zuriani Mat Zaid; Muhammad Shahrul Ifwat Ishak; Rossidi Usop; Normadiah Daud (Brazilian Journals, 2026)
Non-Indexed Publication